LAW AS A SOCIAL AND CULTURAL PHENOMENON AND LAW CIVILIZATIONS - Kucuk , Андрей Николаевич (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2014)
The article focuses on understanding of law, in particular as a social and cultural phenomenon. Attention is drawn to the fact that there can be no universal definition of law, as it is an integral part of a particular culture. Law should be considered only in the context of specific social values, certain law civilization through the prism of law polycentrism.